O povo em Maquiavel como guardião da liberdade - Dal Castel, Karen Elena Costa (2013)
This dissertation is to analyze the roles of the people in Machiavelli through the classic The Prince and Discourses on the first decade of Livy. For this, we sought to conceptualize people in the Machiavellian theory, by having some theoretical foundation as McCormick, Larivaille, Bignotto, among others. We have also tried to approach the concept of freedom in Machiavellian freedom as non-domination concept - recovered by Philip Pettit. The goal is to focus on the role of the people in political life, with the main hypothesis the same as an active agent in the polis and guardian of liberty. So diverges is interpretive trends dating back to Strauss, Mansfield, Sasso, Chabod, Sfez and Skinner, which people attach to a passive role in politics, serving as a tool to Prince and wishing not only be overwhelmed. This paper advocates the role of the people as key to maintaining freedom. Machiavelli delegates this function Talks, explaining that he did not want to seize it. The people preserving the freedom since they do not want to be overcome and, at the same time, does not have the desire of the Great command